The Legal and Moral Principles as Guidelines for Carrying Out Official Duties - Saputro, Aries; Radian Salman (Yuridika, 2024)
Law and morals are related as an ideal value in the formation of law, because morals are considered universal values "‹"‹that should ideally characterize every legal formation, with the hope that morality in the law can produce good behavior for legal subjects and objects. These morals and laws are in our administrative law, in this case the executive. The problem that is difficult to solve is the problem of corruption, where the act is legally and morally not good or wrong. Anti-corruption regulations are in place and the establishment of the Corruption Eradication Commission reveals that the problem of corruption in our country is not resolved and is even more systematic. Ideally, with the advancement of civilization and the strengthening of moral values "‹"‹as the basis for rules, corruption will decrease to its lowest point from year to year as a government develops. Then, if this law represents a moral value, then the court decision, which is the law, can also contain moral values. As an example also regarding court decisions by state administration officials that are not implemented voluntarily, this can be equated with blatant disobedience to the law making state administration officials arrogant.   Normative juridical analysis used in research includes legal and regulatory theory. Therefore, in order to achieve conformity regarding the morals and behavior of state officials in carrying out their duties, there is a close connection between the bad morals of state officials and behavior that violates the law. The good morals of state officials will make the behavior of state officials high and far from breaking the law.